O processo de constituição da cadeia do biodiesel no estado de Mato Grosso - Ferreira, Geraldo Alves (Universidade Federal de São Carlos, 2011)
The search for renewable energy sources, clean, puts the state of Mato Grosso in the forefront when it comes to biodiesel production, the institutional environmentcreated from the 70's with the modernization of agriculture in the state, facilitated the development Agroindustrial Complex of Soy - CAIS and consequently the biofuel industry that has great relevance to the state's economy. Thus, this paperaims to show the main process of establishing the chain of biodiesel in the state ofMato Grosso on the assumption that the chain of biodiesel is developed with high interdependence of the agroindustrial complex of soy in Mato Grosso. To collectthe data we used a structured questionnaire and semi structured, the researcher presents the guidelines, but also gave the respondent the option of mentioning other points considered relevant and which were not addressed. The questionnaires were administered personally by the author and some others, sente-mails requesting information for institutional aid in the understanding of the relationships of the actors present in this chain. The results indicate the existence of a strong link in the chain of biodiesel with soybean agro-industrial complex in the state and that the production of alternative raw materials for the replacement of soybeans in the biodiesel production chain, is still in its infancy, there is noproduction sufficient scale to offer a competitive with soybeans.
Keywords: Engenharia de produção; Ambiente institucional; Agricultura - modernização; Complexo agroindustrial da soja; Biodiesel; Institutional environment; The modernization of agriculture; Agro-industrial complex soy biodiesel; ENGENHARIAS::ENGENHARIA DE PRODUCAO